Dose-dependency of dexamethasone on the analgesic effect of interscalene block for arthroscopic shoulder surgery using ropivacaine 0.5%: A randomised controlled trial. Issue 9 (September 2015) - Woo, Jae Hee; Kim, Youn Jin; Kim, Dong Yeon; Cho, Sooyoung
Abstract : BACKGROUND: Dexamethasone prolongs the duration of single-shot interscalene brachial plexus block (SISB). However, dose-dependency of dexamethasone as an adjuvant for SISB remains insufficiently understood. OBJECTIVE: The objective of this study is to evaluate the effect of different doses of dexamethasone on the duration of SISB using ropivacaine 0.5%. DESIGN: A randomised, double-blind controlled trial. SETTING: Single university tertiary care centre. PATIENTS: One hundred and forty-four patients scheduled for elective arthroscopic shoulder surgery were allocated randomly to one of four groups. INTERVENTIONS: Patients received 12 ml of ropivacaine 0.5% in 0.9% saline (control group), or containing dexamethasone 2.5, 5.0 or 7.5 mg for SISB. MAIN OUTCOME MEASURES: The primary endpoint was the time to the first analgesic request. Pain scores and adverse effects were also assessed up to 48 h postoperatively. RESULTS: Inclusion of dexamethasone 2.5, 5.0 and 7.5 mg resulted in significant ( P  < 0.001) increases in time to the first analgesic request by factors of 1.6, 2.2 and 1.8, respectively. The percentages of patients not requiring analgesics in the first 48 h postoperatively with dexamethasone 0.0, 2.5, 5.0 and 7.5 mg were 3, 22, 39 and 33%, respectively ( P  < 0.001). There were no significant effects on pain scores or incidences of adverse effects. CONCLUSION: Dexamethasone demonstrated significant beneficial dose-dependent effects on duration to the first analgesic request, the number of patients not requiring analgesics and analgesic use in the first 48 h after SISB for arthroscopic shoulder surgery. There were no significant effects on pain scores or incidences of adverse effects. TRIAL REGISTRATION: the trial was registered with the Clinical Trial Registry of Korea: https://cris.nih.go.kr/cris/index.jsp. Identifier: KCT0001078